SPECTRAL AND DYNAMICAL HINTS ON THE TIME SCALE OF PREPARATION OF THE 5 APRIL 2003 EXPLOSION AT STROMBOLI VOLCANO - Carniel R.; Di Cecca M.; Ortiz R. (My University, 2006)
Stromboli volcano is well known for its continuous strombolian activity. Moreover, the volcano occasionally shows effusive phases, the latest in 1985-1986. On 28 December 2002 Stromboli entered a new effusive phase, accompanied by different paroxysmal events that led to considerable hazards for inhabitants and tourists on the island of Stromboli. On 30 December 2002 a major sector collapse affected the Sciara del Fuoco slope and initiated a tsunami. On 5 April 2003 a powerful explosion, which can be compared in size with the most recent explosion in 1930, covered a large part of the normally tourist accessible summit area with bombs. As this explosion was not forecasted, although the island was by then effectively monitored by a dense deployment of instruments, in this paper, we tackle the problem of highlighting the time scale of preparation of this event and conduct a search for possible precursors. For this purpose, we analyze the seismic data preceding the paroxysm with spectral and dynamical methods, highlighting that this paroxysmal event can be seen as the final result of a dynamical phase that started at least 2.5 h before the event. Therefore, this is the time scale during which the search can and should be made for possible precursors. Moreover, the application of the "material failure forecast" method suggests that this final dynamical phase may be just the final acceleration of a process that was building up for at least several days prior to the event. © 2006 NRC Canada.